Peran Brand Love Dalam Memediasi Pengaruh Brand Trust terhadap Purchase Intention pada Pengguna Iphone Di Kota Gorontalo - Angraini, Rezki; Musafir, Musafir; Arifin, Arifin (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to analyze and explain the Influence of Brand Love's Role in Mediating the Influence of Brand Trust on Purchase Intention on iPhone Users in Gorontalo City. The method used in this study is a quantitative approach with descriptive presentation. Data collection used by using a survey, the number of samples in this study was 90 respondents. The analysis method used is SEM PLS 3.0. The results of the study show that. Brand Trust (X) has an indirect effect on Purchase Intention (Y) Mediating Brand Love (Z) on iPhone Products in Gorontalo City.